A Review of Virtual Touch Interaction Systems - Rizwan Ali Abro (Sukkur IBA University, 2020)
Virtual touch has opened a new dimension in the field of Human Computer Interaction (HCI). Enabled with the motion and gesture detection techniques, it allows manual interaction with virtual environments. Virtual environments are built for performing tasks which are typically achieved using hands in the real world, such as handling objects. An analysis on wearables, graspable and touchable haptic devices used in multiple fields is discussed in this study. This paper reviews the design aspect as well as the usage of the haptic devices along with trendy practices that involved in generating satisfactory touch sensations.